Relevance Of The â€œContiguityâ€ Doctrine To International Territorial Disputes, Including The Spratly Islands Dispute - Sharma, Surya P (Journal of Malaysian and Comparative Law, 2019)
In the nineteenth century, unappropriated territories were sometimes claimed on the basis of geographical proximity, i.e. contiguity, or territorial propinquity, the idea being that a state which is closet to the territory in question should have title. In Africa the colonial powers employed the hinterland doctrine to explain this basis of claim during the late nineteenth century. Their argument was that a state occupying a coastral strip was entitled to an unspecified portion of the hinterland.